Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5222/j.child.2017.158
|View full text |Cite
|
Sign up to set email alerts
|

Baby Walker Use and Its Consequences in a Group of Turkish Children

Abstract: Baby Walker Use and Its Consequences in a Group of Turkish ChildrenObjective: Although not recommended, nowadays baby walkers (BWs) are commonly used by many parents in the pre-walk period of children. Therefore studies are needed about the use and effects of BWs on child health and development to provide evidence based recommendations to parents. The aim of this study was to determine the frequency of BW-use, and related injuries among baby walker users, to investigate the effect of BW use on gross motor deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
4
1
1
Order By: Relevance
“…While 68.5% of the mothers in the present study reported the use of a baby walker for the child, this rate has been reported as 57.5% in a study in Istanbul, 75.4% in Ankara, and 90% in Middle Eastern countries [44][45][46] . Home accidents related to the use of a baby walker were determined at the rate of 18.3% in the current study, which was higher than the rates of 7.8% and 13.5% reported in previous studies 44,45 . The disadvantages of using a baby walker, and if used, the necessity for close supervision of the child, should be explained to parents.…”
Section: Discussioncontrasting
confidence: 60%
“…While 68.5% of the mothers in the present study reported the use of a baby walker for the child, this rate has been reported as 57.5% in a study in Istanbul, 75.4% in Ankara, and 90% in Middle Eastern countries [44][45][46] . Home accidents related to the use of a baby walker were determined at the rate of 18.3% in the current study, which was higher than the rates of 7.8% and 13.5% reported in previous studies 44,45 . The disadvantages of using a baby walker, and if used, the necessity for close supervision of the child, should be explained to parents.…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand it is was reported that falling down from the baby walker was common the most form of the accident related to baby walker [15]. During our well child visits we observed that BW use ( Figure 1) was common among toe-walkers, and a small-multicentered crosssectional study confirmed this observation [8].…”
Section: Introductionsupporting
confidence: 71%
“…Multicentered prospective studies are also needed on this issue. In the literature, to our knowledge, there is only one study reporting the relationship between gait disturbance and BW use [8]. In this multi-centered cross-sectional study, it was found that toe-walking was significantly high in the BW group.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations